2019
DOI: 10.3390/su11205551
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Land Certification on Sustainable Land Use Practices: Case of Gozamin District, Ethiopia

Abstract: Agroforestry is attracting considerable attention in Ethiopia because of its potential for sustainable land use practices. As land tenure insecurity is a major limiting factor for sustainable land use practices in Ethiopia and developing countries in general, the Ethiopian government launched a rural land certification program to secure land tenure. There are limited empirical studies about the impacts of land certification on sustainable land use practices. To fill this knowledge gap, this study was outlined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 37 publications
(20 reference statements)
1
10
0
Order By: Relevance
“…For instance, Berhanu & Fayera (2005), SARDP (2010) and Belay (2010) indicated that farmers in Amhara region have developed better tenure security after the land certification program. Similarly, Mengesha et al (2019) in their study in Gozamin district of Amhara region found out that there is a positive correlation between land certification and land tenure security.…”
Section: Effects Of Land Certification In Amhara Regionmentioning
confidence: 84%
“…For instance, Berhanu & Fayera (2005), SARDP (2010) and Belay (2010) indicated that farmers in Amhara region have developed better tenure security after the land certification program. Similarly, Mengesha et al (2019) in their study in Gozamin district of Amhara region found out that there is a positive correlation between land certification and land tenure security.…”
Section: Effects Of Land Certification In Amhara Regionmentioning
confidence: 84%
“…Given that, in general, insecurity in land tenure is a major limiting factor in Ethiopia and in developing countries for sustainable use, the government has introduced a Rural Land Certification Program to ensure land tenure. As shown by Mengesha et al (2019), Alemu et al (2020), andAbi et al (2018), as soon as their land was certified, the majority of farmers in Ethiopia practiced sustainable land use. Land certification, therefore, makes a major contribution to sustainable land use.…”
Section: Land Governance and Land Use Decision Makingmentioning
confidence: 98%
“…Nhantumbo and Camargo 2016); analyses of how forest policy instruments and management regimes influence, for good or for worse, sustainability and livelihoods (e.g. Scheba and Mustalahti 2015;Mengesha et al 2019;Gnych et al 2020); and biomass exploitation aiming at more efficient energy production (Chitawo et al 2018).…”
Section: Figure 10 Countries Represented In Eligible Studiesmentioning
confidence: 99%
“…Certification schemes were shown to have positive impact on the adoption of sustainable land use practices, quality of products and the income of adhering landholders (Girma and Gardebroek 2015;Kalonga and Kulindwa 2017;Mengesha et al 2019). However, such schemes depend on tenure security and can be costly for smallholders to adopt, thereby limiting access to 'green' businesses (Damme 2018).…”
Section: Subsistence and Income Diversification Through Forest-based mentioning
confidence: 99%